Affinities of the family Sollasellidae (Porifera, Demospongiae). II. Molecular evidence. - Erpenbeck, D.; Hooper, J.N.A.; List-Armitage, S.E.; Degnan, B.M.; Wörheide, G.; van Soest, R.W.M. (Contributions to Zoology, 2007)
This is the second part of a revision and re-classification of the demosponge family Sollasellidae, and an example of a successful use of combined morphological and molecular data. Sollasella had been a poorly known, long forgotten taxon, placed incertae sedis in the order Hadromerida in the last major revision of the demosponges. It has recently been suggested to belong to Raspailiidae in the order Poecilosclerida due to striking morphological similarities. The present analysis verifi ed this re-classification using molecular markers. Comparing 28S rDNA fragments of Sollasella cervicornis, a newly described species S. moretonensis and a representative set of raspailiid and hadromerid samples. In our analyses Sollasella clearly clusters inside the Raspailiidae clade, and distantly from hadromerid taxa. Supporting morphological hypothesis of Van Soest et al. (2006), that Sollasella is a raspailiid sponge.